2018
DOI: 10.3748/wjg.v24.i21.2279
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and Crohn’s disease endoscopic index of severity: Correlations and concordance

Abstract: AIMTo examine the correlation between magnetic resonance imaging (MRI) and endoscopic index of severity (CDEIS) in patients with Crohn’s disease (CD).METHODSThis was a retrospective study of 104 patients with CD that were treated at the Ruijin Hospital between March 2015 and May 2016. Among them, 61 patients with active CD were evaluated before/after treatment. MRI and endoscopy were performed within 7 d. CDEIS was evaluated. MRI parameters included MaRIA scores, total relative contrast enhancement (tRCE), art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Gastroenterology Research and Practice CRP levels. Although some previous studies showed a significant correlation between CRP levels and inflammation on MRE, this issue is controversial in the literature [37,38].…”
mentioning
confidence: 94%
“…Gastroenterology Research and Practice CRP levels. Although some previous studies showed a significant correlation between CRP levels and inflammation on MRE, this issue is controversial in the literature [37,38].…”
mentioning
confidence: 94%